Factors influencing Social Acceptance of Residential Solar Energy Technology - Nur Shahira Syaza Wan Asnari; Wan Nurul K. Wan Ahmad; Eta Wahab; Alina Shamsuddin (International Journal of Supply Chain Management, 2020)
The world is facing many environmental problems such as global warming due to high demand of energy use, especially our dependency on fossil fuels. The Malaysian government has introduced various policies and programs to promote alternative green energy solutions such as solar energy to address this issue. However, social acceptance of solar energy could influence the feasibility of the energy as an alternative to satisfy the rising demand. Drawing from research survey and the academic literature, this paper explores the factors that could influence social acceptance of residential solar energy project in Malaysia. Data for this study were collected through a survey in Taiping, Perak; a city recognized as the top three most sustainable in the world by the International Tourismus-Börse in 2019. A total of 240 questionnaires were collected from the respondents in Taiping and the data were analysed using descriptive and correlation analysis. This study reveals that knowledge is able to determine society’s perception and change their opposition towards solar energy. In addition, high cost could hinder society’s acceptance of solar energy, thus their willingness to switch to the energy.